The determination of future output from sheep and cattle farms : an investment study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Agricultural Economics and Marketing at Massey University - Scott, Michael Edward (Massey University, 1977)
Agricultural supply analysis is concerned with the practical and important problems of explaining historical and predicting future patterns of livestock and crop production. Production at the farm level is the foundation of supply at the regional or national level. Decisions which determine the production of the different agricultural products are made at the individual farm level. The collective results of these decisions are the aggregate supplies which are available for export, local consumption or further processing. The objectives of supply analysis are to answer three questions: Why has production changed in the past? How may aggregate production be expected to change in the future? How may production be expected to respond to alternative controls contemplated by policy makers in Government? In developing countries policy makers need to know what is required to provide sufficient incentive for farmers to expand production. Highly developed countries such as the United States have sometimes suffered from an oversupply of particular products. Policy makers in these countries may need to know how production can be reduced, or diverted to more profitable products.
Keywords: New Zealand Agriculture; Beef industry; Sheep industry; Economic aspects